Bone marrow transplantation in canine mucopolysaccharidosis I. Effects within the central nervous system. - Shull, R M (1987)
Five dogs with mucopolysaccharidosis I, a model of human Hurler/Scheie syndrome, were transplanted with marrow from phenotypically normal littermates at 5 mo of age. At 3 and 9 mo posttransplantation, biopsies of cerebral cortex, liver, and cerebrospinal fluid were obtained. The alpha-L-iduronidase levels in these tissues were 0.8-7.4, 26-45, and 6.3-14.9% of the paired donor tissues, respectively. Although iduronidase was present in relatively low levels in the recipients' brains and cerebrospinal fluid at both biopsy times, reduction in brain glycosaminoglycan (GAG) was comparable to that observed in liver. Ultrastructural studies of cells within the transplanted dogs' brains showed less lysosomal distension and storage product than in affected, nontransplanted, littermate controls. The most marked clearing of stored GAG was in cells surrounding blood vessels, but decreased lysosomal storage in neurons and glial cells was also observed. Urinary GAG excretion also decreased to near normal levels by 5 mo posttransplantation.